A review of multivariate methods for multimodal fusion of brain imaging data - Sui, Jing; Adali, Tülay; Yu, Qingbao; Chen, Jiayu; Calhoun, Vince D. (Journal of neuroscience methods, 2012)
► A comprehensive survey of 7 multivariate methods applied in multimodal fusion. ► Comparison of the assumptions, goals, data reduction, data input for each model. ► Classifying methods in two ways: (1) the need of priori/input data. (2) optimization priority. ► Providing examples in brain imaging data application for each method. ► Offer a reference that helps readers understand the trade-offs of various methods. The development of various neuroimaging techniques is rapidly improving the measurements of brain function/structure. However, despite improvements in individual modalities, it is becoming increasingly clear that the most effective research approaches will utilize multi-modal fusion, which takes advantage of the fact that each modality provides a limited view of the brain. The goal of multi-modal fusion is to capitalize on the strength of each modality in a joint analysis, rather than a separate analysis of each. This is a more complicated endeavor that must be approached more carefully and efficient methods should be developed to draw generalized and valid conclusions from high dimensional data with a limited number of subjects. Numerous research efforts have been reported in the field based on various statistical approaches, e.g. independent component analysis (ICA), canonical correlation analysis (CCA) and partial least squares (PLS). In this review paper, we survey a number of multivariate methods appearing in previous multimodal fusion reports, mostly fMRI with other modality, which were performed with or without prior information. A table for comparing optimization assumptions, purpose of the analysis, the need of priors, dimension reduction strategies and input data types is provided, which may serve as a valuable reference that helps readers understand the trade-offs of the 7 methods comprehensively. Finally, we evaluate 3 representative methods via simulation and give some suggestions on how to select an appropriate method based on a given research.